1991
DOI: 10.1021/es00019a013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of biofilm accumulation on porous media hydrodynamics

Abstract: Laboratory-scale porous media biofilm reactors were used to evaluate the effect of biofilm accumulation, measured as the average thickness along a 50-mm flow path, on media porosity, permeability, and friction factor. Media tested consisted of 1-mm glass spheres, 0.70-mm sand, 0.54-mm sand, and 0.12-mm glass and sand. Pseudomonas aeruginosa was used as inoculum and 25 mg L_1 glucose substrate was continuously supplied to the reactor. Reactors were operated under constant piezometric head conditions resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
224
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(240 citation statements)
references
References 14 publications
13
224
3
Order By: Relevance
“…This phenomenon has been observed in laboratory experiments [Cunningham et al, 1991;McCarty, 1999, 2000;Baveye, 1992a, 1992b] and in field studies [Vecchioli et al, 1980]. Clogging closer to the injection well could lead to permeability reduction that may be underestimated if the high heterogeneity of clogging is not properly taken into account (Table 4).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This phenomenon has been observed in laboratory experiments [Cunningham et al, 1991;McCarty, 1999, 2000;Baveye, 1992a, 1992b] and in field studies [Vecchioli et al, 1980]. Clogging closer to the injection well could lead to permeability reduction that may be underestimated if the high heterogeneity of clogging is not properly taken into account (Table 4).…”
Section: Discussionmentioning
confidence: 80%
“…When As noted by Cunningham et al [1991], who assumed a continuous biofilm, growth is initially exponential and identical in all the pores regardless of size. Growth eventually levels off when substrate becomes limiting, and this occurs at different times depending on the size of the channels.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the initial bioavailable Fe(III) content was changed from 5.0 mol/g in the column experiments to 2.5 mol/g in the field. This is likely due to the fact that the column experiment used the <4 mm fraction of the sediment, which Multiple studies have shown that it is easier to clog a porous medium with fine-grained materials (29)(30)(31). The current estimate is based on the assumption that the system is a homogeneous system with uniform distributions of aquifer properties.…”
Section: Resultsmentioning
confidence: 99%
“…The first dual-species biobarrier model (1.7) with standard Monod kinetics (1.9) has been validated in with the porous media experiments done by Cunningham et al (1991) for a 1 × 1 cm long PU foam cube with 0.70 mm, in diameter. In our first simulation, we consider initial and boundary conditions for S C that correspond to a high nutrient concentration experiment, i.e.…”
Section: Morphological Studies Of Immobilized Bacterial Cells On Puf mentioning
confidence: 99%